Through the lens of workers’ motivation: does it relate to work–family relationship perceptions? - Lopes, Sílvia (2022)
Workers’ motivations and the work–family relationship are two subjects that have been capturing the attention of researchers and practitioners. However, to date, little is known about the link between the two subjects. Thus, this research aimed to investigate the relationships among each type of motivation conceptualized in self-determination theory and work–family conflict, work–family enrichment, and work–family balance. In addition, the current study intended to investigate the relationships among work–family conflict, work–family enrichment, and Work–family balance. Data were collected through a self-administered questionnaire. To test the hypotheses, the PROCESS macro was used. The results suggested that intrinsic motivation is negatively associated with work–family conflict and positively associated with work–family enrichment and work–family balance. Additionally, identified regulations seem to be positively associated with work–family enrichment and work–family balance. However, contrary to expectations, this study revealed a positive relationship between introjected regulation and work–family enrichment and work–family balance. Concerning external regulation (material and social) and amotivation, globally, the findings were consistent with the hypotheses, i.e., the higher the external regulation and amotivation, the higher work–family conflict and the lower the work–family enrichment and work–family balance. Moreover, the higher the work–family conflict, the lower the work–family balance, and the higher the work–family enrichment, the higher the work–family balance. Theoretical and practical implications are discussed.